Aqueous synthesis of highly luminescent AgInSe2/ZnS core/shell nanocrystals - Thi Thu Huong, Tran; Thi Hiep, Nguyen; Thu Loan, Nguyen; Van Long, Le; Thanh Tung, Nguyen; Thi Dieu Thuy, Ung; Reiss, Peter; Kim, Jae Yup; Quang Liem, Nguyen (Vietnam Journal of Science and Technology, 2024)
Ternary I-III-VI chalcopyrite-type nanocrystals (NCs) range among the most important alternative materials to Cd-based NCs. Within this materials family, AgInSe2 (AISe) presents a narrower bandgap than widely studied AgInS2 (AIS), making it more suitable for numerous applications. At present, it remains a long-standing challenge to directly synthesize high-quality AISe core and AISe/ZnS core/shell NCs in aqueous solution at atmospheric pressure. In this work, we describe their synthesis using glutathione and citric acid as dual stabilizers. First, to form AISe core NCs, the Se precursor is injected into a solution containing the Ag and In complexes at 96 °C for 20 min. In the second step, the AISe/ZnS core/shell structure is created by growing the ZnS shell on the AISe NCs surface at 90 °C for 60 min. The synthesized AISe and AISe/ZnS core/shell NCs are characterized using X-ray diffraction, transmission electron microscopy, and UV-Vis absorption and photoluminescence for optical spectroscopies. After the growth of the ZnS shell, AISe/ZnS core/shell NCs exhibit higher photostability and emit intense luminescence at a wavelength of 680 nm with an impressive quantum yield (QY) of 30 %, which represents a threefold higher than the AISe core NCs. These properties make the aqueous soluble AISe/ZnS core/shell NCs favorable candidates for lighting, displays, and biological imaging applications.